Pengaruh Perendaman Kembang Telang (Clitorea ternatea) Pada Tingkat Konsentrasi Asam Sulfat yang Berbeda Terhadap Persentase Perkecambahan, Kecepatan Berkecambah dan Panjang Hipokotil : Effect of Butterfly Pea (Clitoria ternatea) Soaking at Different Sulfuric Acid Concentrations on Germination Percentage, Rate, and Hypocotyl Length - Sulendre, I Wayan; Tarsono, Tarsono; Mangun, Mardiah; Teguh, Mumammad; Syahrir, Syahrir; Safitri, Dewi (Fakultas Peternakan Universitas Jambi, 2026)
Background: Utilization of legume plants rich in protein and highly favored by livestock is an effective approach to improving the quality of ruminant livestock feed. In this context, Butterfly Pea (Clitoria ternatea) is widely used as livestock feed due to the high protein content, organic matter digestibility, energy digestibility, and metabolizable energy of 21–29%, 69.7%, 66.6%, and 12.4 MJ/kg, respectively. During development, there are still obstacles posed by the low germination rate of Butterfly Pea seeds because of strong seed dormancy. Purpose: Therefore, this research aimed to examine the effects of soaking Butterfly Pea seeds in different concentrations of sulfuric acid solutions on germination percentage, rate, and hypocotyl length. Methods: A Completely Randomized Design (CRD) was used with three treatments and five replications, namely P1 (15% sulfuric acid for 15 minutes), P2 (30% sulfuric acid for 15 minutes), and P3 (45% sulfuric acid for 15 minutes). Data were analyzed using analysis of variance (ANOVA). Results: The results showed that increasing sulfuric acid concentration influenced all measured parameters. Germination percentage increased from 25.60 ± 2.45% in P1 to 29.60 ± 2.99% in P2, reaching 28.80 ± 3.87% in P3. The highest germination rate was observed in P3 (5.10 ± 0.21%/day), with hypocotyl length also showing the highest value at 7.15 ± 0.41 cm. Conclusion: P3 at 45% concentration for 15 minutes was most effective in increasing germination and initial growth of Butterfly Pea seeds.